Prevalence and Associated Factors of Problematic Use of Smartphones Among Adults in Qassim, Saudi Arabia: Cross-sectional Survey - Abdulrahman Al-Mohaimeed; Mansour Alharbi; Ilias Mahmud (JMIR Publications, 2022)
BackgroundThe Kingdom of Saudi Arabia (KSA) ranks third globally in smartphone use. Smartphones have made many aspects of life easier. However, the overuse of smartphones is associated with physical and psychosocial problems. ObjectiveThe aim of this paper is to estimate the prevalence and associated factors of problematic use of smartphones among adults in the Qassim region of KSA. MethodsWe enrolled 715 participants using cluster random sampling for this cross-sectional survey. We assessed the problematic use of smartphones using the short version of the Smartphone Addiction Scale. ResultsWe estimated the prevalence of problematic smartphone use among adults at 64% (453/708). Multivariable logistic regression analysis suggested that students are 3 times more likely to demonstrate problematic use compared with unemployed individuals (P=.03); adults using more than five apps are 2 times more likely to demonstrate problematic use compared to those using a maximum of three apps (P=.007). Protective factors against problematic smartphone use include using apps for academic (odds ratio [OR] 0.66; P=.04) or religious needs (OR 0.55; P=.007) and having a monthly family income of 5001-10,000 SAR (Saudi Riyal; US $1300-$2700; OR 0.46; P=.01) or 10,001-20,000 SAR (US $2700-$5400; OR 0.51; P=.03) compared to the <1501 SAR (US $400) income group. ConclusionsWe reported a very high prevalence of problematic use of smartphones in KSA. Considering its negative impact on physical and psychosocial health, public health programs should develop preventive strategies.